Highgate Cemetery Image Practices in Past and Present - Scolari, Baldassare (Media and Religion | Medien und Religion, 2020)
The famous Highgate Cemetery in London has stimulated people's imaginations for over 150 years. Accompanied by an introduction to the history of the cemetery, this book provides fourteen in-depth articles which describe and analyse the site of Highgate Cemetery and the practices and images that have been both linked to it and provoked by it. These articles highlight different aspects, including the cemetery's scenic and architectural setting, the use of religious signs and symbols on its gravestones, the interplay between its parkland environment and the representations of nature on its monuments, its past and contemporary social and religious meanings as well as its depictions in literature, film and guided tours. The articles provide new and surprising insights into one of London's most intriguing sites. With contributions by Dolores Zoé Bertschinger, Carla Danani, Natalie Fritz, Anna-Katharina Höpflinger, Ann Jeffers, Marie-Therese Mäder, Alexander Darius Ornella, Niels Penke, Daria Pezzoli-Olgiati, Sean Ryan, Alberto Saviello, Baldassare Scolari, Paola von Wyss-Giacosa, Michael Ulrich The famous Highgate Cemetery in London has stimulated people's imaginations for over 150 years. Accompanied by an introduction to the history of the cemetery, this book provides fourteen in-depth articles which describe and analyse the site of Highgate Cemetery and the practices and images that have been both linked to it and provoked by it. These articles highlight different aspects, including the cemetery's scenic and architectural setting, the use of religious signs and symbols on its gravestones, the interplay between its parkland environment and the representations of nature on its monuments, its past and contemporary social and religious meanings as well as its depictions in literature, film and guided tours. The articles provide new and surprising insights into one of London's most intriguing sites. With contributions by Dolores Zoé Bertschinger, Carla Danani, Natalie Fritz, Anna-Katharina Höpflinger, Ann Jeffers, Marie-Therese Mäder, Alexander Darius Ornella, Niels Penke, Daria Pezzoli-Olgiati, Sean Ryan, Alberto Saviello, Baldassare Scolari, Paola von Wyss-Giacosa, Michael Ulrich